Temporal patterns of honey bee (Apis mellifera L.) mitochondrial DNA variation in the archipelago of Azores (Portugal) - Pinto, M. Alice (2011)
Morphological and molecular studies have been carried out on different Mediterranean and Atlantic island populations of honey bees. A previous genetic survey of the Azorean honey bees, carried out by De la Rúa and colleagues (2006), showed their genetic distinctiveness from continental populations and their close relationship with NW African populations. Herein we present the results of a more comprehensive survey (samples collected from all the islands of the archipelago) of the mitochondrial DNA variation exhibited by the honey bee populations of Azores. Using previously obtained results from honey bee samples collected in 2001, we assess the temporal maternal variation of these populations over a 9 year time frame.